Atomistic insight into Al-Mg friction stir welding process via molecular dynamics simulation - Van-Thuc Nguyen; Van Huong Hoang; Thanh Tan Nguyen; Tran Ngoc Thien; Xuan-Tien Vo; Van Thanh Tien Nguyen (PLoS ONE, 2026)
Friction stir welding (FSW) has recently intrigued academics’ interest due to advances in high strength, low heat generation, tiny grain size, no melting, and the ability to produce dissimilar welding. It created a weld joint by stirring and applying stress to the interface of two metallic plates with a high-hardness tool. The impact of tool pin geometries during the stirring process and the existence of the friction stir welding tool are typically disregarded, particularly in molecular dynamics (MD) simulations, despite a large number of earlier reports. Therefore, in this report, the dissimilar welding joint of Mg-Al by friction stir welding (FSW) is investigated via MD simulation. The effects of travel speed, rotation speed of the tool, and tool pin geometry on the formation of Mg-Al weld joints are examined. The results indicate that Al atoms mix more effectively in the Mg plate than Mg atoms do in the Al plate. Improving the travel speed from 500 to 2000 m/s leads to a more severe atomic strain distribution, leading to a high-temperature zone up to 1000 K and an amorphous fraction of 18.8%. Moreover, the plastic deformation and high-temperature zone tend to become greater when the rotation speed increases. The mechanical atomic mixing level fluctuates with rotation speed, reaching a maximum value at 12 rad/ps. Rotating at 12 rad/ps also leads to the highest levels of mechanical atomic mixing and amorphous atoms. Considering the tool pin geometry, the rectangular prism and cone geometries gain a higher level of heating. The triangular and tube geometries create a better stirring effect. The results enhance atomic-level understanding of the mechanics of the FSW process. The following studies should evaluate the influence of offset distance and tool angle on the material flow of base metals.